Diagnostic efficiency of hybrid imaging using PSMA ligands, PET/CT, PET/MRI and MRI in identifying malignant prostate lesions - Scobioala, Sergiu (Ann Nucl Med, 2021)
OBJECTIVE: The objective of this study was to assess the accuracy of (68)Ga-PSMA-11 PET/MRI, (18)F-PSMA-1007 PET/CT, (68)Ga-PSMA-11 PET/CT, and multiparametric (mp)MRI for the delineating of dominant intraprostatic lesions (IPL). MATERIALS AND METHODS: 35 patients with organ-confined prostate cancer who were assigned to definitive radiotherapy (RT) were divided into three groups based on imaging techniques: (68)Ga-PSMA-PET/MRI (n = 9), (18)F-PSMA-PET/CT (n = 16) and (68)Ga-PSMA-PET/CT (n = 10). All patients without PSMA-PET/MRI received an additional mpMRI. PSMA-PET-based automatic isocontours and manual contours of the dominant IPLs were generated for each modality. The biopsy results were then used to validate whether any of the prostate biopsies were positive in the marked lesion using Dice similarity coefficient (DSC), Youden index (YI), sensitivity and specificity. Factors that can predict the accuracy of IPLs contouring were analysed. RESULTS: Diagnostic performance was significantly superior both for manual and automatic IPLs contouring using (68)Ga-PSMA-PET/MRI (DSC/YI SUV(70%)—0.62/0.51), (18)F-PSMA-PET/CT (DSC/YI SUV(70%)—0.67/0.53) or (68)Ga-PSMA-PET/CT (DSC/YI SUV(70%)—0.63/0.51) compared to mpMRI (DSC/YI—0.47/0.41; p < 0.001). The accuracy for delineating IPLs was not improved by combination of PET/CT and mpMRI images compared to PET/CT alone. Significantly superior diagnostic accuracy was found for large prostate lesions (at least 15% from the prostate volume) and higher Gleason score (at least 7b) comparing to smaller lesions with lower GS. CONCLUSION: IPL localization was significantly improved when using PSMA-imaging procedures compared to mpMRI. No significant difference for delineating IPLs was found between hybrid method PSMA-PET/MRI and PSMA-PET/CT. PSMA-based imaging technique should be considered for the diagnostics of IPLs and focal treatment modality. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s12149-021-01606-7.